2004 ELECTIONS IN KAZAKHSTAN: STRATEGY AND TACTICS OF THE POLITICAL PARTIES - BULUKTAEV, Yuri (CENTRAL ASIA AND THE CAUCASUS, 2005)
Elections to the Majilis, the country’s lower house of parliament, were held on 19 September and 3 October (repeat elections took place in 22 of the 67 one-member districts), 2004. According to the Central Election Commission, nearly 5 million people participated in the voting (56.5% of the active electorate). The names of 77 deputies—67 one-member and 10 party—are well known. Thirty members of the new parliament also belonged to previous deputy corps (a total of 49 balloted). Almost 80% of the parliament members are Kazakhs, and 20% are Russians and representatives of other nationalities, there are 69 men and 8 women, all of whom have higher education, with the average age being 51 (the youngest is 33 and the oldest 73). The party breakdown is as follows: Otan has 53 members (7 on the party list, 35 officially nominated by the party in one-member districts, and 11 self-nominees who are party members); the AIST bloc [abbreviation for the Agrarian-Industrialist Union of Workers, which in Russian means “stork”] has 14 members (one on the party list, 10 official one-members, 3 self-nominees); the Asar party, 4 (one on the party list and three official one-members); the Ak zhol party, 2 (one on the party list and one self-nominee); and the Democratic Party has one official member from a one-member district and 3 non-party deputies.1The latest election campaign was distinguished by its interparty intrigues. After all, elections give a significant boost to inner party development, and the preparations for them have an impact on the breakdown in political forces in the country. Twelve political parties, comprising the format of a party system, competed for deputy seats. The configuration of this system was set forth in the Law on Political Parties which came into force in 2002